Socialization of green logistics on wire waste management as a commercial plate basket product - Lolyka Dewi Indrasari; Ana Komari; Afiff Yudha Tripariyanto; Jamilatus Sa'idah (Community Empowerment, 2022)
Utilization of wire waste is feasible to be produced as a plate basket product. The partner who has implemented this innovation is UKM Putu Alwy Jaya. The community service team conducted socialization with the topic "green logistics". This topic is in accordance with the conditions that are being experienced by partners. The purpose of this activity is to increase the role of green logistics in products made from waste wire with selling value. The implementation method includes lectures, discussions, questions and answers and evaluations. Based on the results of the aspirations of the participants involved, it was stated that it was important to recapitulate the inventory of wire waste material every time an order was made to the supplier. Then, calculate the economic order quantity as a point of ordering in the future to minimize material delays. Scheduling optimization is related to the production period. Improving the function of work tools to speed up the production process of plate baskets is the main step. Straightening tools, cutting tools and packing techniques are closely related to green logistics. Therefore, the estimated time estimate, arriving at the destination, product condition, packaging condition is an achievement in green logistics.